No apparent pharmacokinetic interactions were found between henagliflozin: A novel sodium‐glucose co‐transporter 2 inhibitor and glimepiride in healthy Chinese male subjects. - Que, Linling; Huang, Kai; Xiang, Xuemei; Ding, Ying; Chu, Nannan; He, Qing (Journal of Clinical Pharmacy & Therapeutics, 2022)
What is known and objective: Henagliflozin is a novel selective sodium‐glucose co‐transporter 2 (SGLT2) inhibitor with similar inhibitory effect to ertugliflozin. Glimepiride is widely used to treat type 2 diabetes mellitus (T2DM) with few cardiovascular side effects. In the present study, we aimed at evaluating the pharmacokinetic (PK) interactions between henagliflozin and glimepiride. Methods: An open‐label, single‐centre, single‐arm, 3‐period, 3‐treatment, self‐control study was conducted in twelve healthy Chinese male subjects. During each study period, subjects received a single oral dose of glimepiride 2 mg, multiple oral doses of henagliflozin 10 mg or a combination of the two drugs. Serial blood samples were collected 24 h post‐dosing for PK analyses. Finger‐tip blood glucose was also tested for safety evaluation. Results and discussion: Co‐administration of henagliflozin with glimepiride did not affect their plasma PK profiles. For henagliflozin, the 90% confidence intervals for the geometric mean ratio (GMR) for the maximum plasma concentrations at steady‐state (Cmax ss) and the area under the plasma concentration–time curve during a dosing interval at steady‐state (AUCτ, ss) of combination therapy to henagliflozin alone were 1.00 (0.93–1.08) and 1.00 (0.98–1.02), respectively. For glimepiride, the corresponding values of combination therapy to glimepiride alone were 1.00 (0.88–1.13) for maximum plasma concentrations (Cmax), 0.91 (0.84–0.99) for the area under the plasma concentration–time curve from 0–24 h (AUC0‐24h) and 0.91 (0.83–1.00) for the plasma concentration–time curve from 0 h to infinite (AUC0‐inf), respectively. All values fell within the equivalence range of 0.8–1.25. All monotherapies and combination therapy led to no serious adverse events and were well tolerated. What is new and conclusion: Multiple doses of henagliflozin did not exert a significant change on glimepiride PK profiles and a single dose of glimepiride had little effect on henagliflozin blood concentration. Thus, henagliflozin can be co‐administered with glimepiride without dose adjustment of either drug.